DINAMIKA KEAMANAN KAWASAN TIMUR TENGAH DALAM PERSAINGAN KEKUATAN IRAN DAN AMERIKA SERIKAT - Deni Irawan (Dauliyah Journal of Islamic and International Affairs, 2021)
The security dynamics in the Middle East Region are highlighted by the interaction of countries in the Middle East region. The interaction between Iran and the United States has become an interesting phenomenon recently related to Iran’s rapid economic and military development. This condition will a ect the balance of power in the Middle East region. The United States as a hegemonic power in the last few decades saw the development of Iran’s military power as a catalyst for the instability of the Middle East region, it appears that the US is reorienting the orientation of defence policy in the Paci c to the Middle East. The existence of two countries in the e ort to seize dominance in the Middle East region will have an impact on the security of the Middle East region. Therefore this article will try to discuss the security dynamics of the Middle East region in the competition of two powers, the United States and Iran. The discussion will begin by analyzing the relationship between the dominance of inter-regional interaction in the Middle East region and describing US domination as a major force in the Middle East which is rivalled by Iran through the development of military power and will also discuss US defence policy in response to the development of Iranian military forces in the region the Middle East, where competition between the two forces is predicted to increase in the con ICT in the Strait of Hormuz.